Barry Goldwater and the remaking of the American political landscape - Shermer, Elizabeth Tandy (UPCC book collections on Project MUSE. History., 2013)
Barry Goldwater lost the race for the presidency in 1964, but his conservative agenda sparked a movement that has had profound and far-reaching effects on American politics and society. This is a long-overdue reconsideration of the life, times and legacy of a polarizing politician who is as reviled as he is revered.